2012
DOI: 10.1002/jso.23077
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori genotype and polymorphisms in DNA repair enzymes: Where do they correlate in gastric cancer?

Abstract: Our results indicate the importance of H. pylori and APE-1 genotypes in the gastric carcinogenesis. Also, support the hypothesis of a decrease of PARP-1 wild-type activity in older individuals. Taken together these data may be an important clue to understand the role of low-virulence strains of H. pylori in gastric carcinogenesis and point the importance to analyze the polymorphisms as a group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Our data show a higher frequency of the heterozygous genotype TG, followed by the wild-type TT and the homozygous variant GG. A similar distribution was observed in a study conducted in Poland [25], China [26], Turkey [27] and northeastern Brazil [28] in others cancers. The Asp148Glu polymorphism has been associated with an increased risk of colorectal [25], lung [29] and head and neck [30] cancers.…”
Section: Discussionsupporting
confidence: 86%
“…Our data show a higher frequency of the heterozygous genotype TG, followed by the wild-type TT and the homozygous variant GG. A similar distribution was observed in a study conducted in Poland [25], China [26], Turkey [27] and northeastern Brazil [28] in others cancers. The Asp148Glu polymorphism has been associated with an increased risk of colorectal [25], lung [29] and head and neck [30] cancers.…”
Section: Discussionsupporting
confidence: 86%
“…APE-1 expression is increased in gastric cancer and other malignancies and it is increased in gastric epithelial cells by H. pylori infection. These results suggest that it plays a role in carcinogenesis [30] and, interestingly, APE-1 is known to regulate oxidative stress, chemokine expression, and apoptosis [31].…”
Section: Regulation Of Host Response To Infectionmentioning
confidence: 92%
“…Zhang et al then showed that the CC genotype could increase the risk of GC jointly with CagA(+) H. pylori infection. Silva-Fernandes et al showed that rs1136410 in PARP1 was associated with the strains of H.pylori infected and that the C allele carriers had a higher proportion of highvirulence strains of H. pylori [67]. These studies suggest that the SNP could exert pressure on the bacteria and influence the outcome of the infection [67].…”
Section: Dna Repairmentioning
confidence: 99%
“…Silva-Fernandes et al showed that rs1136410 in PARP1 was associated with the strains of H.pylori infected and that the C allele carriers had a higher proportion of highvirulence strains of H. pylori [67]. These studies suggest that the SNP could exert pressure on the bacteria and influence the outcome of the infection [67]. However, Li et al studied the role of rs1136410 in the evolution of precancerous gastric lesions in a cohort of 1281 H. pylori-seropositive subjects and found no positive association.…”
Section: Dna Repairmentioning
confidence: 99%